Studi Fenomenologis Mekanisme Pemungutan Pajak yang Bersumber dari Anggaran Pendapatan Belanja Daerah (Studi Kasus pada Sekretariat Daerah Kabupaten Padang Pariaman) - Rescy Herrico; Charoline Cheisviyanny (Wahana Riset Akuntansi, 2019)
This study discusses the understanding and knowledge of treasurers about taxation, problems related to tax collection from APBD funds and solutions to tax problems in the Padang Pariaman District Secretariat using an institutional theory perspective. The research approach used is descriptive-qualitative. This study discusses from three different perspectives, namely the rule makers represented by the Pariaman KP2KP and the KPP Pratam Padang Satu,The implementation rules are represented by the shipping partner. Questionnaires, interviews and documentation are used for the data collection process, known as triangulation.The results showed that the treasurer's understanding and knowledge were at a sufficient level. The problem of tax collection from APBD funds is the lack of understanding of taxation, treasurer violates the rules, treasurer negligent of obligations, there has never been socialization and unclear rules regarding PPN,the solution related to tax collection from APBD funds is a transaction with a PKP partner and has an NPWP, partners are asked to take care of SKB and increase socialization, and conduct gross up.Keywords: Taxation Problems from APBD, Institutuinal theory